Mus-Ayo a loss-restoration heterotopic museum for coping with grief - Delos Reyes, Sofia Dominique P.
Where do the memories of what people lose go? In the post COVID-19 pandemic time, memories for grieving the losses of Filipinos are now stored in digital spaces, as well as the communal spaces for remembering the loved ones. This comprehensive design project aims to bridge the gap between the physical and digital spaces of storing memories that may help people to cope with grief. This project applied the nonlinear process of Stroebe & Schut's (1999) Dual Process Model of Grief that interprets coping of grief as an oscillation between the loss-orientation and restoration-orientation stressors. The proposal is Mus-Ayo, a museum for coping with grief that incorporates the concept of lualhati and dalamhati wherein the dalamhati spaces are the exhibits focusing on grief work, while the lualhati spaces are the ones dedicated for attending to life changes. The structure is a space-frame intersection of two domes wherein the exhibits are located at the intersection, making it accessible both for public and private users. Due to the time constraints of the project, the writer recommends exploring more technology that can be integrated with the museum spaces aside from VR therapy rooms.